2018
DOI: 10.3390/su10114293
|View full text |Cite
|
Sign up to set email alerts
|

BIM-Based Incremental Cost Analysis Method of Prefabricated Buildings in China

Abstract: In order to achieve the sustainable growth of its urbanization and natural resources, China has been making great efforts to develop prefabricated construction technologies. However, the high incremental cost of prefabricated buildings (PRBs) is a fundamental obstacle to the latter. The current study mainly focuses on analyzing the incremental cost of the on-site construction stage. It is hard to comprehensively identify the incremental cost composition without considering the incremental cost caused by prefab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…The evaluation of energy consumption was different than the extant research, which demonstrated there is an obvious energy savings benefit from adopting modular prefabrication [32,61]. According to the case project, electricity and diesel oil consumption in prefabricated residential building construction is higher by 27% and 41% compared with conventional construction, respectively, because electricity consumption increases greatly due to scaffolding and vertical transportation and diesel oil consumption increases greatly due to the trucking required to install protective steel grids and the truck cranes needed to unload prefabricated components.…”
Section: Difference Of Sustainable Performancementioning
confidence: 77%
See 1 more Smart Citation
“…The evaluation of energy consumption was different than the extant research, which demonstrated there is an obvious energy savings benefit from adopting modular prefabrication [32,61]. According to the case project, electricity and diesel oil consumption in prefabricated residential building construction is higher by 27% and 41% compared with conventional construction, respectively, because electricity consumption increases greatly due to scaffolding and vertical transportation and diesel oil consumption increases greatly due to the trucking required to install protective steel grids and the truck cranes needed to unload prefabricated components.…”
Section: Difference Of Sustainable Performancementioning
confidence: 77%
“…Cao et al demonstrated that prefabrication has a clear advantage in material consumption, energy use, and water discharge [28]. In addition, many studies have focused only on one or a very limited number of indicators to discuss the benefit of prefabricated building, for example, waste generation [29,30] and incremental costs or cost savings [31,32]. Tam and Hao pointed out that construction waste was greatly reduced in various on-site activities [30].…”
Section: Introductionmentioning
confidence: 99%
“…e cost of prefabricated construction is usually higher than traditional cast-in-place construction methods due to the unsound standard system, weak modular design ability, and low efficiency for scale production [11,12]. It is estimated that using prefabricated construction may lead to an incremental construction cost of about 260 CNY per unit construction area (m 2 ) [13,14]. Most contractors are unwilling to adopt prefabricated construction in order to pursue the maximization of economic benefits [15].…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely used in a lot of countries due to the benefits [3]. Prefabricated buildings are also very popular in China [4]. However at present, the floor plan design of the prefabricated house in China still follows the traditional house floor plan design method, and even applies the traditional house plane directly, resulting in problems in the market such as an unreasonable distribution of the suite types of the fabricated house, a low utilization rate of the space of the suite types, an unreasonable plan size with too much variation, a lack of flexibility in the space design, etc.…”
Section: Introductionmentioning
confidence: 99%